Performance Comparison of JIT and JET Protocols on the OBS Networks - Alaa Jamal Abd; Mohammed Joudah Zaiter (Journal of Techniques)
Over the past few years, internet traffic has been explosive growth due to users' need for more applications and services. All these developments on the internet need more bandwidth. The Optical Burst Switching (OBS) mechanism along with Wavelength-Division-Multiplexing (WDM) technology is very useful in meeting the high bandwidth requirements. However, the OBS network uses a one-way resource reservation mechanism, as well as it is a buffer lack at the intermediate (core) node. Therefore, the OBS network depends on contention resolution mechanisms to achieve acceptable levels of performance. In this paper, the Deflection Routing (DR) mechanism is used to overcome contention. The performance of the OBS network has been estimated by executing Just-In-Time (JIT) and Just-Enough-Time (JET) signaling reservation protocols with the DR. NCTUns-6.0 simulator was employed to verify the performance of the OBS network based on two metrics: throughput and packets dropped in the network. The results show that the bandwidth resources utilization in the OBS network with JET and DR (OBS-JET-DR) is better than in the OBS network with JIT and DR (OBS-JIT-DR). However, the average number of packets dropped in OBS-JET-DR is less than OBS-JIT-DR by 21%. In addition, the throughput of OBS-JET-DR has increased by 4% compared with OBS-JIT-DR.